2000
DOI: 10.1021/bk-2001-0778.ch021
|View full text |Cite
|
Sign up to set email alerts
|

Radiation and Chemistry in Nuclear Waste: The NOx System and Organic Aging

Abstract: We describe results that advance the understanding of radiation effects in high level waste (HLW) stored at DOE sites. The scientific issues on which we focus include: a) reactions of primary radicals (e -, OH, and H) of water radiolysis with NO3-/ NO2-b) redox chemistry of NO x radicals and ions, c) degradation mechanisms and kinetics of organic components of HLW, and d) interfacial radiolysis effects in aqueous suspensions and at crystalline NaNO 3 interfaces. Understanding these effects and the chemical rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…be generated in high level waste as a result of the radiolytic decomposition of nitrate and nitrite. 22,23 The XANES spectra of Tc(CO) 2 (NO) and fac-Tc(CO) 3 would be similar. Given the similarity of the XANES spectra of the Tc(I) carbonyl complexes, assignment of the non-pertechnetate species to a particular species is not conclusive although Tc(CO) 3 (gluconate) 2-provides an excellent fit to the observed XANES spectrum of the non-pertechnetate species.…”
Section: Manuscript Textmentioning
confidence: 95%
“…be generated in high level waste as a result of the radiolytic decomposition of nitrate and nitrite. 22,23 The XANES spectra of Tc(CO) 2 (NO) and fac-Tc(CO) 3 would be similar. Given the similarity of the XANES spectra of the Tc(I) carbonyl complexes, assignment of the non-pertechnetate species to a particular species is not conclusive although Tc(CO) 3 (gluconate) 2-provides an excellent fit to the observed XANES spectrum of the non-pertechnetate species.…”
Section: Manuscript Textmentioning
confidence: 95%
“…These reactions, of course, have high activation energies. Meisel et al (1991aMeisel et al ( , 1991bMeisel et al ( , 1993Meisel et al ( ,2000 observed that gas generation continued after the radiolysis of the waste had been stopped and concluded that chemical reactions continued as the unstable organic and inorganic intermediates formed in the radiolytic reaction decomposed. Work in other laboratories has confirmed this concept and demonstrated that the radiolytic processes are synergistically coupled with other chemical reactions to fragment and oxidize the original complexants and solvents.…”
Section: Rpp-6664 Revmentioning
confidence: 99%
“…The quantitative kinetic reaction model has been extended to include evaluation of the rate of oxidation of formate and glycinate ions Meisel et al 2000). The chemical reactions are shown in Figure 3-6.…”
Section: A Quantitative Model For the Oxidation Of Formate And Glycinmentioning
confidence: 99%
See 2 more Smart Citations